2011 Brazilian Symposium on Games and Digital Entertainment 2011
DOI: 10.1109/sbgames.2011.17
|View full text |Cite
|
Sign up to set email alerts
|

Agents Behavior and Preferences Characterization in Civilization IV

Abstract: Player Modeling is becoming an important feature in Digital Games. It basically consists in understanding and modeling the player characteristics and behaviors during the game and has been mainly used to improve the games artificial intelligence, making games more adaptable to different players. In this paper, we try to characterize the preference of the players using a novel approach in games: we use mathematical regressions to characterize players behavior, looking for functions that best fit these behaviors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Since a match may have, at most, 460 turns, we can summarize a whole match with 460 observations. In [7], we were able to show that the evolution of some of these indicators is able to represent different preferences when analyzed along several matches.…”
Section: Civilization IV and Its Agents Preferencesmentioning
confidence: 90%
See 4 more Smart Citations
“…Since a match may have, at most, 460 turns, we can summarize a whole match with 460 observations. In [7], we were able to show that the evolution of some of these indicators is able to represent different preferences when analyzed along several matches.…”
Section: Civilization IV and Its Agents Preferencesmentioning
confidence: 90%
“…Finally, in a previous work [7], we characterized some Civilization IV agents behaviors with linear regressions. We showed that some agents' game indicators, when analyzed individually, can be linearly separable between agents with different preferences, and drew conclusions about preferences in relation to the time in the game (passage of turns), other preferences, and the gameplay.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations